2021
DOI: 10.21203/rs.3.rs-355283/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal Study of Boxing Therapy in Parkinson’s Disease, Including Adverse Impacts of the COVID-19 Lockdown

Abstract: Background: Parkinson’s Disease (PD) is a highly prevalent neurodegenerative disease whose incidence is increasing with an aging population. One of the most serious manifestations of PD is gait instability, leading to falls and subsequent complications that can be debilitating, even fatal. Boxing therapy (BT) uses gait and balance exercises to improve ambulation in people with PD, though its efficacy has not yet been fully proven. Methods: In the current longitudinal observational study, 98 participants with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…These results may be a reflection of the complex interplay between the many different factors that are related to balance control in PD, and we presume that balance interventions for PD will most likely need to take a multiple systems approach [25,[39][40][41]. Additionally, typically boxing trainings incorporate multimodal exercises including different agility, strength, and aerobic activities [17][18][19][20][21] that would challenge balance. Even the boxing drills, shadow boxing and speedbag drills will ultimately require dynamic weight shifting and balance tasks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results may be a reflection of the complex interplay between the many different factors that are related to balance control in PD, and we presume that balance interventions for PD will most likely need to take a multiple systems approach [25,[39][40][41]. Additionally, typically boxing trainings incorporate multimodal exercises including different agility, strength, and aerobic activities [17][18][19][20][21] that would challenge balance. Even the boxing drills, shadow boxing and speedbag drills will ultimately require dynamic weight shifting and balance tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Boxing is one such popular and novel alternative training methods. Just as in other medical conditions (i.e., obesity [15] or stroke [16]), preliminary studies have demonstrated the some positive effects of boxing on balance, mobility, and quality of life in people with PD [17][18][19][20]. Another study showed that self-perceived QOL improvements were maintained throughout 20 weeks of non-contact group-based boxing training, despite lack of improvements in disease severity [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation